Enhanced delivery of antisense oligonucleotides with fluorophore-conjugated PAMAM dendrimers - Yoo, Hoon (Oxford University Press, 2000)
PAMAM dendrimers are cationic polymers that have been used for the delivery of genes and oligonucleotides to cells. However, little is known about the behavior of dendrimer–nucleic acid complexes once they reach the cell interior. To pursue this issue, we prepared dendrimers conjugated with the fluorescent dye Oregon green 488. These were used in conjunction with oligonucleotides labeled with a red (TAMRA) fluorophore in order to visualize the sub-cellular distribution of the dendrimer–oligonucleotide complex and of its components by two-color digital fluorescence microscopy. The 2′-O-methyl antisense oligonucleotide sequence used in these studies was designed to correct splicing at an aberrant intron inserted into a luciferase reporter gene; thus effective delivery of the antisense agent results in the expression of the reporter gene product. The dendrimer–oligonucleotide complex remained associated during the process of uptake into vesicular compartments and eventual entry into the nucleus. Since the pharmacological activity of the antisense compound was manifest under these conditions, it suggests that the dendrimer–oligonucleotide complex is functionally active. A surprising result of these studies was that the Oregon green 488-conjugated dendrimer was a much better delivery agent for antisense compounds than unmodified dendrimer. This suggests that coupling of relatively hydrophobic small molecules to PAMAM dendrimers may provide a useful means of enhancing their capabilities as delivery agents for nucleic acids.